Toán nâng cao

TrangKM

Học sinh mới
Thành viên
29 Tháng ba 2017
40
16
16
18

Nữ Thần Mặt Trăng

Cựu Mod Toán
Thành viên
TV BQT tích cực 2017
28 Tháng hai 2017
4,472
5,490
779
Hà Nội
THPT Đồng Quan
$1)(a-b)^2+(b-c)^2+(c-a)^2=4(a^2+b^2+c^2-ab-ac-bc)
\\\Leftrightarrow (a-b)^2+(b-c)^2+(c-a)^2=2(2a^2+2b^2+2c^2-2ab-2bc-2ca)
\\\Leftrightarrow (a-b)^2+(b-c)^2+(c-a)^2=2[(a^2-2ab+b^2)+(b^2-2bc+c^2)+(c^2-2ca+a^2)]
\\\Leftrightarrow (a-b)^2+(b-c)^2+(c-a)^2=2[(a-b)^2+(b-c)^2+(c-a)^2]
\\\Leftrightarrow (a-b)^2+(b-c)^2+(c-a)^2=0$
Mà $(a-b)^2\geq 0;(b-c)^2\geq 0;(c-a)^2\geq 0 \ \forall \ a,b,c$
$\Rightarrow (a-b)^2+(b-c)^2+(c-a)^2\geq 0$
Dấu '=' xảy ra khi $a=b=c$
.....................
$2)Q=a^4-2a^3+3a^2-4a+5
\\=(a^4-2a^3+a^2)+(2a^2-4a+2)+3
\\=a^2(a^2-2a+1)+2(a^2-2a+1)+3
\\=a^2(a-1)^2+2(a-1)^2+3
\\=(a-1)^2(a^2+2)+3\geq 3$
Dấu '=' xảy ra khi $a=1$
Vậy...
 
  • Like
Reactions: TrangKM
Top Bottom